2021
DOI: 10.1002/prop.202100099
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Physical Properties of Gravitationally Decoupled Anisotropic Solution in 5D Einstein‐Gauss‐Bonnet Gravity

Abstract: In this paper we present two new classes of solutions describing compact objects within the framework of five‐dimensional Einstein‐Gauss‐Bonnet (EGB) gravity. We employ the Complete Geometric Deformation (CGD) formalism which extends the Minimal Geometric Deformation (MGD) technique adopted in earlier investigations to generate anisotropic models from known isotropic solutions. The two solutions presented arise from mimicking the constraint for the pressure and density respectively which generate independent d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 86 publications
0
10
0
Order By: Relevance
“…[32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49]). Even this framework has been used widely in several scenarios such as 2 + 1 space-times [50][51][52][53][54][55], higher dimensions [56,57], asymptotically (A-)dS space-times [58], for axially symmetric systems and rotating black holes [59], hairy black holes [60][61][62], Cosmology [63,64], solutions in the background of Reissner-Nordström space-time [65][66][67], modified gravity theories [68][69][70][71][72][73][74][75][76][77][78], as well in braneworld gravity [79][80]…”
Section: Introductionmentioning
confidence: 99%
“…[32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49]). Even this framework has been used widely in several scenarios such as 2 + 1 space-times [50][51][52][53][54][55], higher dimensions [56,57], asymptotically (A-)dS space-times [58], for axially symmetric systems and rotating black holes [59], hairy black holes [60][61][62], Cosmology [63,64], solutions in the background of Reissner-Nordström space-time [65][66][67], modified gravity theories [68][69][70][71][72][73][74][75][76][77][78], as well in braneworld gravity [79][80]…”
Section: Introductionmentioning
confidence: 99%
“…We now only need to solve the second system corresponding to θ -sector which depends on the undetermined deformation function ψ(r ), in order to find the complete solution for energy-momentum tensor T eff μν . In GR, a wide variety of approaches have been adopted to obtain the deformation function, ψ(r ) [24,[29][30][31] but very few in the context of 5D EGB gravity [26][27][28]. In this work we mimic the seed energy density (r ) to θ 0 0 (r ) i.e.…”
Section: Minimally Deformed Polytropic Solution In Egb Gravitymentioning
confidence: 99%
“…Then, it may not be possible to embed the stellar compact object to vacuum space-time. But, if we assume that new contributions arising from θ μν are confined within the stellar interior [24,28], then the stellar compact object will remain embedded into a true Boulware-Deser vacuum space-time (52). Now we the fix easily the arbitrary constant parameters by joining of the interior (51) and exterior (52) spacetimes across the boundary.…”
Section: Exterior Space-time and Matching Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the recent research results in GR, f (R, T) and f (G) gravity theories can be seen in the references. [44][45][46][47][48][49][50][51][52][53][54] In this connection, the first systematic approach for MGD and extended MGD in 5D EGB gravity was proposed by Maurya et al [55,56] to obtain the exact solution of the compact star model. Recently, Maurya et al [57] have shown the impact of the decoupling parameter and the EGB constant on the maximum mass limit on minimally deformed neutron star models.…”
Section: Introductionmentioning
confidence: 99%